THE EFFECT OF THE USE OF ANTI-DIABETES INSULIN ON THE LONG OF CARE OF CORONA VIRUS DISEASE - 2019 (COVID - 19) PATIENTS IN PRIMA MEDAN ROYAL HOSPITAL - setia wati br sitepu; irza Haicha Pratama; Andre Budi; Duwina Puspita Sari (Jambura Journal of Health Sciences and Research, 2022)
Latar Belakang: Penyandang Diabetes Militus  memiliki risiko tinggi tertular Covid 19 dan memilik prognosis yang buruk apabila kita  terinfeksi Covid 19. Tujuan penelitian mengetahui pengaruh penggunaan obat insulin dan  terapi kombinasi terhadap lama rawatan  penyembuhan pasien Covid-19.Metode: Penelitian ini merupakan penelitian yang bersifat analitik observasional   untuk melihat pengaruh penggunaan obat anti diabetes Insulin dan Terapi Kombinasi terhadap lama rawatan pasien Covid di Rumah Sakit Umum  Royal Prima. Dengan desain penelitian cross sectional, penelitian dilakukan instalasi rekam medis  Rumah Sakit Umum  Royal Prima Medan pada bulan Desember  2020 -Juni 2021. Populasi dalam penelitian ini adalah seluruh pasien covid-19 dengan diabetes mellitus yang dirawat tercatat dalam catatan medik di RSU Royal Prima pada bulan desember-juni dengan jumlahsampel 2045, populasi sebanyak 173 dengan Teknik simple random sampling. Hasil: Dari 173 pasien Covid-19paling banyak dengan penggunaan terapi kombinasi yaitu 132 orang dengan rerata lama 9,67 hari dengan standart deviasi 4,619. Dari 23 orang dengan rapid/short acting lama rawatan rerata 6,78 dan standard deviasi 4,022 dan dari 18 orang dengan penggunaan obat Long acting lama rawatan 7,11 dengan standart deviasi 4,601 dan hasil uji Oneway-Anova menunjukkan diperoleh sig 0,003 0,05 yang berarti terdapat pengaruh penggunaan obat insulin dan  terapi kombinasi terhadap lama rawatan  penyembuhan pasien Covid-19. Kesimpulan: terdapat pengaruh penggunaan obat insulin dan  terapi kombinasi terhadap lama rawatan  penyembuhan pasien Covid-19. Kata Kunci: Covid 19; DM; Lama Rawatan; Obat Insulin  Abstract                Background: People with diabetes mellitus have a high risk of contracting Covid 19 and have a poor prognosis if they are infected with Covid 19. \-The purpose of the study was to determine the effect of using insulin and combination therapy on the length of treatment for Covid-19 patients. Methods: This type of analytic research is observational with a cross sectional research design, the study was carried out by the installation of medical records at the Royal Prima General Hospital in Medan in December 2020 -June 2021. The population in this study were all Covid-19 patients with diabetes mellitus who were treated recorded in the medical records. at RSU Royal Prima in December-June with a total population of 173 with a simple random sampling technique. Results: Of the 173 Covid-19 patients, the most used combination therapy, namely 132 people with an average duration of 9.67 days with a standard deviation of 4.619. From 23 people with rapid/short acting the average length of stay was 6.78 and the standard deviation was 4.022 and from 18 people with long-acting drugs the length of stay was 7.11 with a standard deviation of 4.601 and the results of the Oneway-Anova test showed sig 0.003 0.05. which means that there is an effect of using insulin and combination therapy on the length of treatment for Covid-19 patients. Conclusion: there is an effect of using insulin and combination therapy on the length of treatment for Covid-19 patients. Keywords: Covid 19; DM; Length of Treatment; Insulin Drugs